EXPLAINING A VIRTUAL RELATIONSHIP: PROSES PENETRASI SOSIAL PADA PENDIDIKAN TINGGI SELAMA PEMBELAJARAN ONLINE - Putri Maulina; Anhar Fazri; Rahmah Husna Yana; Muzakkir Muzakkir (SOURCE : Jurnal Ilmu Komunikasi, 2022)
Since the beginning of 2020, the Covid-19 pandemic has changed learning models and communication models at the university level. The face-to-face learning process is shifted to an online learning process using various distance learning applications. This has implications for the communication patterns that occured between students and students. This study aims to examine how the process of interpersonal communication that emphasizes aspects of developing communication relationships that are formed between students and their colleagues during the distance learning process. The theoretical approach used in this study is Social Penetration Theory which emphasizes several stages: 1) orientation stage; 2) Exploratory Affective Exchange Stage; 3) Exploratory Exchange Stage) and 4) Stable Exchange Stage. Furthemore, the method used in this research is descriptive qualitative using online survey tools and closed interviews. The population of this research is active students at Teuku Umar University class of 2019 and 2020, with a total of 20 informants. The result showed online learning provided a different virtual communication pattern in the relationship development process. The informants prioritized the virtual images displayed and more active communication repossession with a good attitude. Relationship development is also at the stage of forming comfort and not being intimate. With a relationship cycle back and forth, especially when they met in real.